Neutrophil dysfunction triggers inflammatory bowel disease in G6PC3 deficiency. Issue 6 (15th September 2020) - Goenka, Anu; Doherty, John A.; Al‐Farsi, Tariq; Jagger, Christopher; Banka, Siddharth; Cheesman, Edmund; Fagbemi, Andrew; Hughes, Stephen M.; Wynn, Robert F.; Hussell, Tracy; Arkwright, Peter D
Abstract: The glucose‐6‐phosphatase catalytic subunit 3 ( G6PC3 ) encodes a ubiquitously expressed enzyme that regulates cytoplasmic glucose availability. Loss‐of‐function biallelic G6PC3 mutations cause severe congenital neutropenia and a diverse spectrum of extra‐hematological manifestations, among which inflammatory bowel disease (IBD) has been anecdotally reported. Neutrophil function and clinical response to granulocyte colony‐stimulating factor (G‐CSF) and hematopoietic stem cell transplantation (HSCT) were investigated in 4 children with G6PC3 deficiency‐associated IBD. G6PC3 deficiency was associated with early‐onset IBD refractory to treatment with steroids and infliximab. The symptoms of IBD progressed despite G‐CSF treatment. In vitro studies on the patients' blood showed that neutrophils displayed higher levels of activation markers (CD11b, CD66b, and CD14), excessive IL‐8 and reactive oxygen species, and increased apoptosis and secondary necrosis. Secondary necrosis was exaggerated after stimulation with Escherichia coli and could be partially rescued with supplemental exogenous glucose. HSCT led to normalization of neutrophil function and remission of gastrointestinal symptoms. We conclude that neutrophils in G6PC3 deficiency release pro‐inflammatory mediators when exposed to gut bacteria, associated with intestinal inflammation, despite treatment with G‐CSF. HSCT is an effective therapeutic option in patients with G6PC3 deficiency‐associated IBD refractory to immune suppressants. Graphical Abstract: Neutrophils in glucose‐6‐phosphatase catalytic subunit 3 deficiency release pro‐inflammatory mediators when exposed to gut bacteria, which is associated with intestinal inflammation that can be treated by hematopoietic stem cell transplantation.